Digital radiographic evaluation of the midpalatal suture in patients submitted to rapid maxillary expansion - Maria de Fátima Batista de Melo; Saulo Leonardo Sousa Melo; Tiago Gorgulho Zanet; Marlene Fenyo-Pereira (Wolters Kluwer Medknow Publications, 2013)
Aims: To analyze the density of the midpalatal suture by means of digital radiographs three months after retention to evaluate if this period of retention is really sufficient for bone repair. Materials and Methods: This prospective study consisted of 31 patients (11 girls and 20 boys) in the mixed or permanent dentition stage, treated using a tooth-tissue borne expanders (Haas). Occlusal digital radiographs were taken at three stages: prior to rapid maxillary expansion (Stage I); immediately after desired maxillary expansion (Stage II); and after three months of retention (Stage III). Radiographs were taken on a dental X-ray machine, set at 70 kVp and 7 mA with an exposure time of 0.04 s. A phosphor storage plate system, imaging plate size n. 2 (35 × 45 × 1.6 mm), was used. Three regions (A, B and C) measured 0.02 mm² were selected for optical density analysis. The difference between the measurements was evaluated with the paired t-test. Results: The optical density was reduced at Stages II and III compared with Stage I. Between-stage comparison showed statistically significant changes for all variables (P < 0.05), with the highest mean optical density at Stage I and the lowest at Stage II, in all groups. Actually, there was an increase in optical density between Stages II and III, but they are reduced compared with Stage I. Conclusion: The results strongly suggest that bone formation did not occur as expected, and that a longer retention period for bone repair may be necessary.